Impact of home-based cognitive or academic intervention on working memory and mathematics outcomes in pediatric brain tumor survivors: the Keys to Succeed pilot randomized controlled clinical trial. Issue 8 (17th November 2022) - Peterson, Rachel K.; Longo, Carmelinda; Cunningham, Todd; Janzen, Laura; Guger, Sharon; Monteiro, Lovetta; Rapson, Robin; Bartels, Ute; Bouffet, Eric; Solomon, Tracy; Mabbott, Donald J.
ABSTRACT: Pediatric brain tumour survivors experience deficits in mathematics and working memory. An open question is whether it is most optimal to target direct cognitive skills (i.e. working memory) or focus on specific academic outcomes (i.e. mathematics) for in remediation. We conducted a pilot randomized controlled trial to determine the feasibility of comparing a working memory versus mathematics intervention. Pediatric brain tumor survivors (7-17 years) were randomly assigned to Cogmed or JumpMath interventions, or an Active Control/Reading group. All participants received Educational Liaison support and completed ~12-weeks of home-based intervention with weekly, telephone-based consultation in one of the three conditions. Standardized assessments of auditory and visual working memory, mathematics calculation and reasoning were completed pre- and post- intervention. Twenty-nine participants completed the interventions; 94% of parents reported a high degree of satisfaction with the interventions and ease of implementation. Participants in JumpMath demonstrated improved mathematics calculation from pre- to post- intervention (p=0.02). Further, participants in both Cogmed and JumpMath showed evidence of pre- to post- intervention improvements in auditory working memory relative to controls (p=0.01). The Cogmed group also showed improvements in visual working memory (p=0.03). Findings suggest that targeted intervention is feasible in survivors of pediatric brain tumors, though with a relatively low recruitment rate. With preliminary findings of improved calculation and working memory following JumpMath and working memory following Cogmed, this pilot trial lays the groundwork for future programs that investigate different inteCognitiveRehabilitationrventions that may be applied to target the unique needs of each survivor.